Influence of state of health and personality factors of resilience and coping in healthy subjects and those with diabetes - Rivera-Picón, Cristina; Benavente-Cuesta, María Hinojal; Quevedo-Aguado, María Paz; Juárez-Vela, Raúl; Martinez-Tofe, Jesús; Sánchez-González, Juan Luis; Rodríguez-Muñoz, Pedro Manuel (Frontiers in Public Health, 2023)
Introduction Currently, the most common chronic metabolic disease in our society is Diabetes Mellitus. The diagnosis of Diabetes Mellitus supposes an impact for the patient, since it requires a modification in the lifestyle, which demands a great capacity for adaptation and modification of habits. The aim of the study was to determine whether personality factors and health status influence resilience and coping strategies in a sample of healthy and diabetic subjects. Methodology The sample included a total of 401 subjects (201 patients with Diabetes and 200 without pathology). The instruments applied for data collection were: Sociodemographic data questionnaire, the Resilience Scale, the Coping Strategies Questionnaire and The “Big Five” factor taxonomy. The data collection period was approximately 2 years (between February 2018 and January 2020). Results Certain personality factors, such as Emotional Stability, Integrity, Conscientiousness and Extraversion, were positively related to Resilience. Additionally, Emotional Stability, Integrity, and Extraversion were positively associated with Rational Coping. On the other hand, emotional stability, agreeableness and extraversion were negatively related to emotional coping. In relation to health status, the absence of pathology is related to the use of rational strategies more than to the diagnosis of diabetes. Therefore, the participants in this study present different psychological patterns depending on personality and health status. Conclusions The present study shows that the subjects of the sample present different psychological patterns depending on Personality and health status.